2007
DOI: 10.1002/pen.20946
|View full text |Cite
|
Sign up to set email alerts
|

Viscoelastic evaluation of effects of fiber size and composition on cellulose‐polypropylene composite of high filler content

Abstract: The dispersion of filler in resin is an important factor which determines the mobility of a compound in a molder and also the mechanical properties of molded products in wood/plastic composite, especially with high wood filler content. In this report, the dispersion of components in the melt‐mixture of a compound in response to the size of cellulose filler and resin content was examined for compounds with a high content of cellulose in polypropylene by the evaluation of viscoelasticity using a cone rheometer, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 15 publications
0
7
1
Order By: Relevance
“…On the other hand, for hardwood fiberboards, the bending properties for LCNFmixed fiberboard for 1.00 g/cm 3 -density board were higher than those for the control fiberboard. In general, the quality of composite properties mixed with smaller size particles was not improved [27]. Nevertheless, in this study, the properties of fiberboards made with LCNF were much improved compared to wood fiber only.…”
Section: Binding Effect Of Lcnf In Fiberboardcontrasting
confidence: 60%
“…On the other hand, for hardwood fiberboards, the bending properties for LCNFmixed fiberboard for 1.00 g/cm 3 -density board were higher than those for the control fiberboard. In general, the quality of composite properties mixed with smaller size particles was not improved [27]. Nevertheless, in this study, the properties of fiberboards made with LCNF were much improved compared to wood fiber only.…”
Section: Binding Effect Of Lcnf In Fiberboardcontrasting
confidence: 60%
“…Particle size of the LCNF for 200 rpm/32 h was 1/20 that of untreated wood flour (Table 1). In general, the quality of composite properties mixed with smaller size particles was not improved [20]. Nevertheless, in this study the The board densities were almost the same as those shown in Table 2, indicating that the void ratios in the test samples were nearly identical.…”
Section: Binding Effect Of Lcnf In the Wood Flour Boardmentioning
confidence: 45%
“…The highest moduli were found for the board having a WF:CNF of 90:10, which was considered the optimal composition. Increasing the CNF content above 20% caused the moduli to decrease, which was attributable to flocculation of the CNF [6], which likely became more important as pulverization progressed. The mixing condition chosen for this part of the study (i.e., 250 rpm/2 h) was just sufficient to generate a binding effect by the CNF.…”
Section: Resultsmentioning
confidence: 99%